Can Fire and Rescue Services and the National Health Service work together to improve the safety and wellbeing of vulnerable older people? Design of a proof of concept study - Whiting David G; Laybourne Anne H; Lowton Karen; Martin Finbarr C (BMC, 2010)
Abstract Background Older adults are at increased risk both of falling and of experiencing accidental domestic fire. In addition to advanced age, these adverse events share the risk factors of balance or mobility problems, cognitive impairment and socioeconomic deprivation. For both events, the consequences include significant injury and death, and considerable socioeconomic costs for the individual and informal carers, as well as for emergency services, health and social care agencies. Secondary prevention services for older people who have fallen or who are identifiable as being at high risk of falling include NHS Falls clinics, where a multidisciplinary team offers an individualised multifactorial targeted intervention including strength and balance exercise programmes, medication changes and home hazard modification. A similar preventative approach is employed by most Fire and Rescue Services who conduct Home Fire Safety Visits to assess and, if necessary, remedy domestic fire risk, fit free smoke alarms with instruction for use and maintenance, and plan an escape route. We propose that the similarity of population at risk, location, specific risk factors and the commonality of preventative approaches employed could offer net gains in terms of feasibility, effectiveness and acceptability if activities within these two preventative approaches were to be combined. Methods/Design This prospective proof of concept study, currently being conducted in two London boroughs, (Southwark and Lambeth) aims to reduce the incidence of both fires and falls in community-dwelling older adults. It comprises two concurrent 12-month interventions: the integration of 1) fall risk assessments into the Brigade's Home Fire Safety Visit and 2) fire risk assessments into Falls services by inviting older clinic attendees to book a Visit. Our primary objective is to examine the feasibility and effectiveness of these interventions. Furthermore, we are evaluating their acceptability and value to key stakeholders and services users. Discussion If our approach proves feasible and the risk assessment is both effective and acceptable, we envisage advocating a partnership model of working more broadly to fire and rescue services and health services in Britain, such that effective integration of preventative services for older people becomes routine for an ageing population.